Immigration as the main driver of population dynamics in a cryptic cetacean. Issue 2 (11th February 2023) - Tenan, Simone; Moulins, Aurelie; Tepsich, Paola; Bocconcelli, Alessandro; Verga, Alessandro; Ballardini, Marco; Nani, Barbara; Papi, Daniela; Motta, Gabriella; Aguilar, Ana Sanz; Rosso, Massimiliano
Abstract: Empirical evidence about the role and interaction of immigration with local demographic processes in shaping population dynamics is still scarce. This knowledge gap limits our capability to derive a conceptual framework that can be used to inform conservation actions. Populations exposed to nonstationary environment do not converge to a stable stage distribution, implying the need for evaluating the demographic role of both vital rates and stage distribution using appropriate tools. This is particularly important for species with larger generation times like cetaceans. We explored the relative demographic role of vital rates and population structure of a poorly known cetacean, the Mediterranean Cuvier's beaked whale, while accounting for the exposure to nonstationary environments. We performed a retrospective analysis through transient life table response experiments (tLTRE) using demographic rates and population structure of both sexes obtained from an integrated population model. The contribution of immigration to variation in realized population growth rates was 4.2, 7.6, and 12.7 times larger than that of female apparent survival, proportional abundance of breeding females with a 2‐year‐old calf, and proportional abundance of breeding females with a 3‐year‐old calf, respectively. Immigration rate and proportional abundance of breeding females with a 2‐ or 3‐year‐old calf explained, respectively, 65% and 20% of total temporal variability in realized population growth rates. Changes in realized population growth rate between successive years were mainly driven by changes in immigration and population structure, specifically the proportional abundance of breeding females with a 2‐year‐old calf. Our study provides insight into the demographic processes that affect population dynamics and in a cryptic cetacean. We presented an analytical approach for maximizing the use of available data through the integration of multiple sources of information for individuals of different distinctiveness levels. Abstract : Our study provides insight into the immigration and reproductive processes driving population dynamics of a poorly known cetacean, through an analytical approach that maximizes available data, and can be used to better understand the demographic contribution of life‐history traits and population structure and, ultimately, the persistence of cetacean populations.